ORIGIN OF THE BERING SEA SALIENT - Amato J.M.; Toro J.; Moore T.E. (My University, 2004)
Our investigations in Alaska and Russia show that the curved orogen of the Bering Strait region is a composite feature that formed as a result of multiple superimposed events and cannot be related to latest Cretaceous-early Tertiary east-west shortening. Relations interpreted to record east-west shortening include the Chukchi syntaxis, deformation on Seward and Chukotka Peninsulas, the map pattern of Triassic-Jurassic mafic rocks, and plate reconstructions. These relations are reviewed in light of new data and show that the curved orogen cannot have been formed by east-west shortening. For example, the Chukchi syntaxis, the northeastern limb of the orogen, is a primary structural loop that originated during the Brookian orogeny in the Early Cretaceous and therefore predates postulated oroclinal bending. East-west shortening on Seward Peninsula and Chukotka is manifest by low-amplitude, long-wavelength folds that require only small strains. The Seward Peninsula/Yukon-Koyukuk province boundary was previously interpreted as a thrust fault, but it instead may be a left-lateral strike-slip fault. Triassic-Jurassic mafic rocks similar to the Angayucham terrane are found on the northern Chukotka Peninsula, but a better correlation is with rocks farther south in the South Anyui suture zone, resulting in a less-arcuate pattern. Mid-Cretaceous north-south extension in the Bering Strait region has enhanced the curvature of the margin. Recent plate reconstructions indicate that shortening between Eurasia and North America was previously overestimated and that significant east-west convergence probably did not occur in the region during the Tertiary. We conclude that the curved orogen in the Bering Strait region is not a true orocline and instead is a composite structural feature that is best described as a salient.
Keywords: Bering Sea; Mesozoic::Cretaceous; Мезозой::Меловая